Us and Them: The Prince Rupert Fishermen's Co-op and Organized Labour, 1931-1989 - Menzies, Charles (Labour/Le Travailleur, 2001)
Abstract Co-operative forms of enterprise are often held up as a progressive, moderate alternative to the privations of the capitalist market economy. This paper considers the Prince Rupert Fishermen's Co-op and its relations with organized labour in the north of British Columbia. The paper describes a contradiction within the co-op based on the possibilities of social ownership within a market economy. Through a discussion of the escalating labour conflicts between the co-op and its non-member employees the weaknesses of co-operative enterprises are revealed.